Ethnic Identity and Cultural Preservation in White Teeth a Novel by Zadie Smith - Hussein Dizayi, Saman Abdulqadir (International Journal of Psychosocial Rehabilitation, 2019)
This paper analyses the cultural preservation as an ethnic identification in Zadie Smith's novel White Teeth (2000). The novel underlines the significance of legacy and roots while concentrating on the life of Muslim immigrants whose convictions and beliefs are impacted by British culture. The paper investigates how pro colonized immigrants are behaving to preserve their culture among a multicultural society such as Britain's. It also explains the later generations' assimilation to British culture. Depending on post war Britain's cultural theory of Raymond Williams taking culture as a whole way of life.The paper conducts an analytic qualitative method to reach at one of the important findings that is the dynamics of culture is vital in human lives.Furthermore, it reveals its relationship with environments since culture cannot be separated from synaptic elements of social life